2004
DOI: 10.1136/adc.2002.017202
|View full text |Cite
|
Sign up to set email alerts
|

The relative efficacy of two brief treatments for sleep problems in young learning disabled (mentally retarded) children: a randomised controlled trial

Abstract: Background: Settling and night waking problems are particularly prevalent, persistent, and generally considered difficult to treat in children with a learning disability, although intervention trials are few. Scarce resources, however, limit access to proven behavioural treatments. Aims: To investigate the efficacy of a media based brief behavioural treatment of sleep problems in such children by comparing (1) face-to-face delivered treatment versus control and (2) booklet delivered treatment versus controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 20 publications
4
89
0
Order By: Relevance
“…However, it is questionable whether or not a 1-point reduction on a 12-point scale is clinically important; previous work has suggested that at least a 50% reduction in problems is considered by parents to be worthwhile. 45 The unadjusted results of the other instruments tended to favour melatonin but improvements were small. On average, a reduction of 4 points on the 100-point scale was estimated for each domain in the PedsQL Family Impact Module.…”
Section: Questionnairesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is questionable whether or not a 1-point reduction on a 12-point scale is clinically important; previous work has suggested that at least a 50% reduction in problems is considered by parents to be worthwhile. 45 The unadjusted results of the other instruments tended to favour melatonin but improvements were small. On average, a reduction of 4 points on the 100-point scale was estimated for each domain in the PedsQL Family Impact Module.…”
Section: Questionnairesmentioning
confidence: 99%
“…Removed GOSH and Northampton from lists of pharmacies and centres as these centres were never initiated. 7, 37, 39, 45 References to Epworth Sleepiness Scale put back into their original locations in the protocol. In the previous substantial amendment, the removal of the Epworth Sleepiness Scale was described in the substantial amendment form in error.…”
Section: Data Monitoring Committee (Dmc)mentioning
confidence: 99%
See 2 more Smart Citations
“…These involve a detailed assessment, the creation of an individualised behavioural sleep management strategy and time-limited, (typically) face-to-face support as parents implement the strategy. However, despite promising evidence regarding their effectiveness (Vriend et al 2011, McDaid andSloper 2009) these interventions are not routinely available (Montgomery et al 2004).…”
Section: Introductionmentioning
confidence: 99%